2022
DOI: 10.3390/ma15072427
|View full text |Cite
|
Sign up to set email alerts
|

Deflections and Stresses in Rectangular, Circular and Elliptical Insulating Glass Units

Abstract: Insulating glass units (IGUs) are construction elements that react to climatic loads in a specific way. Under the influence of changes in atmospheric pressure and temperature, as well as the effect of wind, the gas closed in the tight gap between the glass panes changes its pressure, which affects the resulting static quantities of the loaded IGUs. The calculation models described in the literature mostly concern rectangular units, however, other shapes are being implemented more and more often in modern archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Taking into account the sensitivity of deformation and the pressure difference in the gap to the linear dimensions of IGUs described in [8,9], it was found that the use of too large a sample was not justified. This was because as the linear dimensions increase there is a significant gas interaction, which requires a large amount of injected gas to cause a significant deflection of the panes and induce stress in the glass.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking into account the sensitivity of deformation and the pressure difference in the gap to the linear dimensions of IGUs described in [8,9], it was found that the use of too large a sample was not justified. This was because as the linear dimensions increase there is a significant gas interaction, which requires a large amount of injected gas to cause a significant deflection of the panes and induce stress in the glass.…”
Section: Methodsmentioning
confidence: 99%
“…Curcija and Vidanovic [11] proposed a model for calculating deflection in multi-glazed IGUs based on numerical solutions of systems of equations. A numerically validated model for calculating static values in rectangular and circular IGUs was proposed by Respondek et al [8,9]. Stratiy [6] presented an analytical and numerical model for estimating the deflection in a double-glazed IGU, also in the range of large deflections.…”
Section: Of 15mentioning
confidence: 99%
See 2 more Smart Citations
“…It may cause a smaller cavity width than near the spacer where the glass is clamped. The shape, size and thickness of the glass will also influence the bending of a glass pane (Feldmeier et al 1984;Buddenberg et al 2016;Respondek et al 2022). To minimize the effect of variation in cavity width due to bending of glass panes, a fixed measuring position in the lower area of the IGU is recommended.…”
Section: Sampling Position On Igumentioning
confidence: 99%